NIHILIZMAS IR NAUJIEJI REALIZMAI. - Šerpytytė, Rita (Problems / Problemos, 2012)
The article deals with the controversy 'concerning reality' -- an ongoing and constantly updated discussion in the contemporary philosophy. The analysis stems from the premises proposed by Maurizio Ferraris -- one of the most prominent initiators and representatives of the so-called 'new realism'. The roots of Maurizio Ferraris's inclination to 'realism' can be recognized in his specific interpretation of Nietzsche's phrase "There are no facts, only interpretations". The article reveals that there is a link between this revised phrase and Ferraris's criticism of modern and postmodern philosophy as well as the concept of reality represented by 'new realism'. The relationship between modernism and postmodernism, the post modern 'loss' of reality, expressed as a 'virgolettazione della realtè' (i.e. putting the reality into commas) is discussed from the perspective of new realism. question is what do these commas mean for reality? Or one could ask together with Gianni Vattimo: "Who would need the truth without commas, and whom would this truth serve?" In fact, Vattimo's ontological hermeneutic and the concept of reality intertwined with interpretation appears as an alternative to Ferraris's position. Finally, the article discloses the affinity of Ferraris's concept with the Jacobi's commonsense take on reality and its relation to nihilism.